Racine’s Phèdrе Translated by Mikhail Muravyev - Alexander D. Ivinskiy (Литературный факт)
The article is devoted to M.N. Muravyov’s translation of the tragedy of Jean Racine’s Phèdre. In the 18th century, Phèdre had not been translated into Russian, so this attempt, although incomplete, is of interest to the history of Russian drama. The article introduces the first three scenes of the first action of the tragedy (the Department of Manuscripts of the Russian National Library, St. Petersburg) into scientific circulation. We linked this text with excerpts from” and Thebaide, or The Enemy Brothers, found in the poet’s handwritten Notebook (the Manuscript Department of the Russian State Library, Moscow). In addition, we found a text that indicates Muravyov’s plans for the translation of Racine’s Iphigénie. Also, in the Notebook, several of Muravyov’s poems were found (“No mind is needed for poetry,” “A poet needs to exercise,” etc.), in which he expresses an almost enthusiastic attitude towards Racine. Another source that we used is Muravyov’s letters to his father, N.A. Muravyov, and sister, F.N. Muravyova, from the Department of Written Sources of the State Historical Museum (Moscow); based on them, we hypothesize that the translation of Phèdre was completed by the beginning of 1776. At the same time, we reconstruct the historical and literary context of Muravyov’s hidden polemic with A.P. Sumarokov, in particular, with his “Opinion in a Dream about French Tragedies.” Rejecting the claims of the “northern Racine” to hegemony in Russian drama, Muravyov highlighted “the real” Racine and M.V. Lomonosov, whose heir he thought of himself.